Avaliação de pastagens tropicais em sistemas de produção de ovinos de corte no nordeste brasileiro - Emerenciano Neto, João Virginio (2012)
He aim of this study was to evaluate the structural characters, herbage accumulation, nutritive value and performance of sheep in different tropical pastures. The treatments were two cultivars and two of the genera Panicum Brachiaria pastures under intermittent stocking and variable stocking rate, in the rainy season. We evaluated the masses and the components of herbage pre grazing in two layers, and after grazing. Chemical analyzes were made of the stems and leaf blades pre grazing in two layers. We used 48 male sheep and whole for the assessment of individual weight gain and area, and anestrous females to adjust the stocking rate. In the cv. Massai showed the highest herbage mass, leaf blades and dead material, and the largest volume density and leaf blade: stem pre grazing. There was no difference among cultivars for the percentage of leaf blade (PLB) in both strata, but the higher the PLB was higher than the bottom. The highest percentage of dead material (PDM) was observed in cvs. Massai and Marandu in the two strata. In cvs. Massai and Piatã were observed lower levels of crude protein in stem and leaf. In stratum 0-25 cm lower nutritional value was observed in the stem in the leaf blades did not grant the nutritional value among the strata. Herbage mass, leaf blade, PLB and proportion of stem in the residue of the Massai pastures were higher than cv. Aruana. There was no difference for efficiencies in harvest leaf and stem between the cultivars. The cv. Massai got the higher accumulation of leaf per cycle per day. Animals kept in grass swards Aruana had the highest average daily gain. The higher stocking rates and earnings per area were observed in grass swards and Marandu Massai. The cultivars are suitable for sheep meat production in the rainy season